The probable factors of insider trading in Malaysian firms prior to acquisition announcement / Majid Sarli ... [et al.] - Sarli, Majid; Tan, Olivia Swee Leng; Aghashahi, Betsabeh; Sarli, Abduljalil (Accounting Research Institute & Faculty of Accountancy, 2014)
The aim of this paper is to deliberate on the subject of nsider trading that is viewed as a financial crime as well as to identify major factors that can contribute to reducing it. In this case, this research is focuses on investigation of companies’ acquisition announcements, which are listed from the traded volumes of Bursa Malaysia between 2008 and 2011. The study useda sample of considered thirty companies and their acquisition announcements are analyzed by examining their Average Cumulative Abnormal Volume Traded (ACAVT) to identify probable insider trading activities. The study affirms consequently, stronger laws, effective rules and regulations are recognized as effi cient approaches to controlling insider trading at the fi nancial markets, while the infl uencing factors on insider trading would be suggested as the proposed conceptual model for further research